Pertanggungjawaban Hukum Influencer Atas Penggalangan Dana Publik: Studi Kasus Penyelewengan Donasi Selebgram: Penelitian - Urbanisasi; Joe Aprella Indra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Public fundraising through digital platforms has become a common practice among influencers for social, humanitarian, educational, and health-related purposes. However, this practice is not free from legal risks, particularly if the collected funds are misused. This study examines the legal accountability of influencers in public fundraising, both civil and criminal, as well as the legal protection for donors. Under civil law, misappropriation of funds can be classified as an unlawful act (Article 1365 of the Civil Code), obligating the influencer to compensate the donors. Under criminal law, such actions may constitute fraud (Article 378 KUHP), embezzlement (Article 372 KUHP), and violations of the Electronic Information and Transactions Law (Article 28 paragraph 1), if misleading information is provided. Donor protection is further reinforced by the Consumer Protection Law and the supervision of the Financial Services Authority (OJK) over official crowdfunding platforms. The study highlights that influencer legal accountability is multidimensional, emphasizing transparency, accountability, and good faith. Implementing good governance, financial reporting, dedicated accounts, and written agreements can serve as preventive measures to reduce legal risks.